ASSOCIATION OF CALCIUM DIETARY WITH BODY MASS INDEX AND BODY FAT : A SYSTEMATIC REVIEW - Fitriana, Ilma; Intan Permatasari, Dela (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: When consuming the necessary amounts of calcium, body mass index (BMI) rises with calcium retention. Aims : This systematic review is to review the association of calcium diet with body mass index and body fat.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 1195 articles, whereas the results of our search on SAGEPUB brought up 14152 articles, our search on SCIENCE DIRECT brought up 21833 articles. The results of the search conducted for the last year of 2014 yielded a total 536 articles for PubMed, 5253 articles for SAGEPUB and 10269 articles for SCIENCE DIRECT. In the end, we compiled a total of  8 papers, 5 of which came from PubMed, 1 of which came from SAGEPUB and 2 of which came from SCIENCE DIRECT. We included eight research that met the criteria.Conclusion: In summary, from eight studies showed that there is no significant changed of body mass index, neither the body fat after received the dietary of calcium.